Computer Literacy and Attitudes Towards e-learning among Bangladeshi Medical Students. - Chowdhury, Nasrin Sultana; Chowdhury, Nurun Nahar; Rabbi, Ferdous; Tabassum, Rehnuma; Ishrat, Sonia (Update Dental College Journal, 2014)
Background: The use of computer has enhanced undergraduate medical education. Computer assisted learning improves performence at examination, develops problem solving skill. The study evaluates computer literacy among the medical students in Dhaka, Bangladesh. Material and Method: Cross sectional descriptive type of study. Data collected by interviwing 322 randomly selected medical student from East West Medical College & Hospital , Dhaka, Bangladesh. Result: Maximum respondents are within 20 -22 yrs (52.8%) female (54.7%), and have average computer skill (61.8%), mostly use for personal purpose (69.6%). Among the user most of them(66.8%) have own computer at home, mostly have laptop (52.2%) from their school period (51.6%).Among most of them consider using this hamper their study (59%), but they found it helpful to improve study (38.2%).They use internet every alternative day, majority for (35.7%) email & browsing. Conclusion: This study showed that students browses net and email for recreation & social communication mostly rather than acquiring knowledge of medical science. Computer is a good source of knowledge of medical science. It can be used to gain update information of medical education. DOI: http://dx.doi.org/10.3329/updcj.v3i1.17977 Update Dent. Coll. j: 2013; 3 (1): 03-06